Simple and sensitive detection of uracil–DNA glycosylase activity using dsDNA-templated copper nanoclusters as fluorescent probes. Issue 22 (23rd May 2016) - Cao, Manman; Jin, Yan; Li, Baoxin
Abstract : DNA-templated copper nanoclusters were used as a fluorescent nano-dye for the uracil–DNA glycosylase (UDG) assay. The proposed method is simple and sensitive. Abstract : Sensitive detection of uracil–DNA glycosylase (UDG) activity is critical for the functional study of UDG and clinical diagnosis. Herein we exploit dsDNA-templated copper nanoclusters (CuNCs) as a fluorescent nano-dye for UDG assay. The UDG-catalyzed uracil removal can liberate ssDNA from the uracil-containing dsDNA substrate, and thus the introduction of Cu 2+ and ascorbate cannot form the fluorescent CuNCs due to the lack of the dsDNA templates. By optimizing the number and location of uracil on the DNA strand, a low detection limit of 0.0005 U mL −1 was achieved. The simple and sensitive method may hold potential applications in UDG-related clinical diagnosis and functional research.